PERAN RUMAH KITAB DALAM PENCEGAHAN KAWIN ANAK DI INDONESIA - Maimunah Mudjahid (Equalita: Jurnal Studi Gender dan Anak, 2019)
Abstract: This study is to examines the role of Social organization, Rumah Kitab in bringing social change for eradicating child marriage in Indonesia. Yayasan Rumah Kitab is a research institute for policy advocacy to fight for human rights of marginalized people such as women, people with disabilities, religious-race-minorities who are discriminated against by gender-biased religious views. The organization focus study is devoted to policy advocacy and organizing using gender analysis. Rumah KitaB works through research, critical religious texts, empowerment of pesantren, organizing women through critical education, educational institutions and marginal people communities. This study is focus on (i) What programs are design for eradicating child marriage and (ii) what is the social force behind the programs.Keyword: eradicating child marriage, Yayasan Rumah Kitab  Abstrak: Penelitian ini dilakukan untuk menganalisis peran dari organisasi sosial Rumah Kitab.  Yayasan Rumah Kitab adalah lembaga riset untuk kebijakan guna memperjuangkan hak-hak kaum termarjinalkan seperti perempuan, orang dengan disabilitas, minoritas suku ras agama yang mengalami diskriminasi akibat pandangan sosial keagamaan yang bias gender. Kajian Rumah KitaB ditujukan untuk advokasi kebijakan dan pengorganisasian dengan menggunakan analisis gender dan feminisme. Rumah KitaB bekerja melalui riset, kajian teks keagamaan kritis, pemberdayaan pesantren, pengorganisasian perempuan melalui pendidikan kritis, lembaga pendidikan dan komunitas warga marjinal. Fokus dari kajian ini adalah (i) program apa yang didesain untuk menghapuskan perkawinan anak dan (ii) apa yang melatar belakangi program tersebut.Kata Kunci: penghapusan perkawinan anak, Yayasan Rumah Kitab